Exploring genetic diversity in an Italian horse native breed to develop strategies for preservation and management. (22nd August 2018) - Ablondi, Michela; Vasini, Matteo; Beretti, Valentino; Superchi, Paola; Sabbioni, Alberto
Abstract: Genetic diversity is a key factor for both adaptation and response to selection. The loss of genetic diversity causes a decrease in individual fitness, and it has a dramatically negative effect on population lifespan in the long term. This study aimed at exploring the genetic diversity at pedigree level of the Bardigiano horse breed, which is a native breed from Italy shaped for living in rural areas. In 1977, the Bardigiano studbook was founded to preserve the breed and for improving its use for riding and draft purposes. Pedigree data contained 9, 469 horses, of which 3, 416 were alive. Demographic and genetic parameters were estimated on subpopulations to evaluate potential genetic diversity differences among breeding and nonbreeding animals, and animals showing different breeding values (EBVs) for an index combining 18 conformation traits. Throughout the studied period, inbreeding steadily increased, reaching in the last birth year cohort a mean value equal to 0.10. The rate of inbreeding per generation, assuming a mean generation interval of 8.74 years, was equal to 1.64%. Moreover, significant differences on both average relatedness and inbreeding among horses with high and low EBVs were shown. Our study unravelled the state of genetic diversity in the Bardigiano breed, highlighting that breeding strategies for optimizing the contribution of breeding animals in the coming generations are needed to ensure long‐term survival of the Bardigiano horse breed.